Commented Translation of Short Stories by Desmond Hogan:Three Tales of Exile - Zimbres, Patricia de Queiroz Carvalho (ABEI Journal, 2017)
The subject of this master’s degree dissertation is the commentedtranslation of three short stories by Desmond Hogan, a contemporary Irish writer still unpublished in Brazil. All three stories deal with the issues of exile and diaspora, of crucial importance in Irish literature. I start out by introducing the author, and proceed to describe the Irish context that conditioned both the themes and the formal aspects of Hogan’s work. The author is then located within the history of the modern Irish literary space, from the early nationalistic manifestations and the high modernism of Joyce and Beckett to the present. In the second part I present my translation of the three short stories in a bilingual format. In my comments, I try to interweave experience and reflection by using the ideas of Henri Meschonnic as presented in his poetics of translation. I identify different aspects of Hogan’s poetics – semantics, rhythm and punctuation – and indicate the manner in which these elements were echoed in the translated text. Lastly, I comment my translation of selected passages.